Analisis Penerapan Metode Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) dan Metode Weighted Aggregated Sum Product Assessment (WASPAS) pada Pemilihan Mekanik Sepeda Motor Terbaik - Sari, Venny Novita; Alinse, Rizka Tri; Sallaby, Achmad Fikri (Building of Informatics, Technology and Science (BITS), 2022)
A company engaged in the sale and repair of motorcycles, of course, requires a reliable and responsible mechanic in his work, for that a motorcycle mechanic is needed in accordance with the terms and conditions required by the motorcycle company. Many mechanics are now opening motorbike repair services, after repairing the motorbike it becomes even worse than before it was repaired, so that it can harm consumers of the repair service. This is because a mechanic only has desperate capital without any experience and abilities that can be guaranteed. Therefore, in selecting the best mechanic, a decision support system is needed with various methods that can be used, such as the TOPSIS method, VIKOR, MOSRA, AHP, MOORA, WASPAS, WP and so on. In this study, the methods used are Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) and Weighted Aggregated Sum Product Assessment (WASPAS) methods. Each alternative will be assessed based on the criteria for Trouble Shooting, Working Time, Education and Warning Letter, then the process of compiling or ranking each alternative is carried out, so that the best alternative or motorcycle mechanic is obtained. The results after applying the MOORA method, namely alternative A2 is the best mechanic with a value of 1.637 and the WASPAS method is the best mechanic in Q2 with alternative A2 with a value of 0.834. Both methods produce the same results, namely the best mechanic is A2